ACTION EFFECTS ON THE PERCEPTION OF MULTISENSORY EVENTS - Finkelshtein, Anna (My University, 2015)
Voluntary actions affect subsequent perception. For example, an action that precedes an auditory stimulus is perceived to have occurred later in time than is actually the case, while the auditory stimulus is perceived earlier in time. This effect is known as intentional binding. Current literature regarding action effects focuses on perception of a single sensory modality while the effects on perception of multiple modalities remain largely unknown. The present thesis explored how actions influenced the timing of perceived multisensory events. Additionally, this thesis investigated differences in voluntary compared to involuntary actions on subsequent perception. In Chapter 2, action effects on perceived onsets of visual and tactile stimuli were explored. This question was extended to other bimodal pairs, including audiovisual and audiotactile, in Chapter 3. Lastly, in Chapter 4, action effects on temporal resolution were investigated. In all the experiments, participants performed a chosen or a fixed button press that followed a bimodal temporal order judgment (TOJ) task. To investigate the influence of spatial proximity between actions and stimuli on binding, in Chapters 2 and 3, each stimulus modality appeared on different sides. In Chapter 4, the critical stimuli appeared at the same location, either close to or far from the preceding action, to explore the effect of action on temporal resolution. The present data provide evidence that actions affect the perceived onsets of multisensory events in an idiosyncratic manner, depending on the subsequent stimuli. Actions appear to preferentially bind to vision, then touch, and lastly, audition, but actions do not always bind to subsequent stimuli. Furthermore, actions degrade temporal resolution of bimodal stimuli. Lastly, the type of action, whether chosen or fixed, did not impact the degree of binding. Together, these data contribute to the action-perception literature, illustrating that our behaviours dynamically affect how we perceive the world.
Keywords: multisensory; temporal order judgment task; point of subjective simultaneity; just noticeable difference; visuotactile; audiovisual; audiotactile; perceived onset; temporal precision; cognition and perception; cognitive psychology; action